Home Environment Characteristics and BMI Z-Score Among Saudi Preschool Children: A Feasibility Study - Mosli, Rana H. (International Journal of Child Health and Nutrition, 2017)
Objective: To assess feasibility of using preschools in Saudi Arabia as a source for collecting nutrition-related data; To examine associations among home environment characteristics and child BMI z-score (BMIz). Methods: Fifty-three (3-5 years old) children and their mothers were recruited from two preschools in Jeddah, Saudi Arabia. Mothers completed a self-administered questionnaire. Child anthropometry was completed using standardized procedures. BMIz was calculated using the WHO growth standards and reference data. Associations between child and home environment variables were tested using Pearson correlation, t-tests and ANOVA. Results: Participation rate in the middle-to high-income preschool was higher compared to the low- to middle-income preschool (27.3% vs. 17.4%, respectively). Increase in child age and maternal BMI were associated with lower maternal playtime with the child (r= -0.31, p= 0.02, and r= -0.38, p= 0.006, respectively). Increase in child age was also associated with lower paternal playtime with the child (r= -0.26, p= 0.05). Paternal playtime with the child was positively associated with both paternal involvement in feeding (r= 0.30, p= 0.03) and regular family mealtimes (r= 0.26, p=0.05). There was a trend of positive association between paternal involvement in feeding and higher child BMIz (r= 0.26, p=0.08). Mean child BMIz was lower when mothers had ³ a college education vs. not (p= 0.04). Greater child screen time was associated with fewer family mealtimes (p= 0.01). Conclusion: Increasing awareness is needed in order to improve feasibility of studies conducted in Saudi preschools; Future work is needed to further establish the associations of home environment characteristics and child obesity.